Attention-Economy Bibliometric Analysis of Fan Culture from 2010 to 2025 - Loso Judijanto (Eastasouth Institute, 2026)
This research proposes to investigate the intellectual growth and research trends of attention economy studies on fan culture scholarship from 2010 to 2025 using a bibliometric method. The study uses performance analysis and science mapping methods to analyze the research publications in the field of fan culture scholarship, focusing on keyword co-occurrence analysis, overlay visualization, density mapping, co-authorship network analysis, and citation analysis. The results show that the research environment has grown from the initial discussion on cultural identity, participatory media, and globalization to more interdisciplinary approaches that combine sustainability, economics, and organizational strategy. The results show that the dominant conceptual foundations are keywords such as sustainable development, sustainability, economics, and culture, while the recent research trends on circular economy, knowledge management, and organizational culture show a new direction towards strategic and sustainable research. Collaboration analysis shows that the research environment is globally networked and dominated by China and the United States, with a growing presence of Europe and Asia-Pacific countries. Overall, the study shows that the transformation of fan culture in the attention economy has become a multidimensional research field that links cultural engagement with economic value creation, sustainability discourse, and global collaborative innovation.